Factores de riesgo que inciden en el desarrollo de la bronquiolitis aguda en niños menores de 2 años. Hospital Martin Icaza. Diciembre 2022 – abril 2023. - Calderón Mancilla, Ingrid Noemy (2023)
Acute bronchiolitis (AB) is considered one of the most common infections of viral origin with children under 2 years of age as a vulnerable group. This condition, classified as acute infectious and affecting the lower respiratory tract in children under 2 years of age, is characterized by the presence of necrosis and inflammation of the bronchial epithelium affecting the lungs bilaterally and diffusely, leading to obstructive ventilatory disability. In this research study we sought to relate the risk factors that affect the development of acute bronchiolitis in children under 2 years of age at the Hospital Martin Icaza Babahoyo - Los Rios, Ecuador in the period April - September 2022, in which a survey was conducted to parents of children under 2 years of age about the symptoms presented by the children and several questions that seek to identify what were the risk factors to which children were exposed before presenting symptoms of acute bronchiolitis. The survey and data collection revealed that most of the children were exposed to respiratory viruses, of which respiratory syncytial virus (RSV), rhinovirus and adenovirus were the most frequently reported risk factors. In this study, a sample of 80 children with acute bronchiolitis between the age range of 0 to 2 years was taken. It is important to point out that a formula was not used for this study. The type of research used was basic, field and cross-sectional, for which an induction, explanation and training about what acute bronchiolitis was, the signs and symptoms that occur when the infection occurs, important characteristics of acute bronchiolitis such as etiology, causes, modifiable and non-modifiable factors were also explained, the causes, modifiable and non-modifiable factors, improvement strategies for acute bronchiolitis, among other important data that may occur before, during and after the clinical picture presented by a child under 2 years of age with acute bronchiolitis.